A review on destination social responsibility: towards a research agenda. Issue 4 (16th February 2023) - Agapito, Dora; Kronenburg, Rosalie; Pinto, Patrícia
ABSTRACT: Destination social responsibility (DSR) is a contemporary construct related to social responsibility efforts at the level of destinations rather than corporations. While DSR has become a salient topic for destinations, research approaches are still fragmented. This work discusses existing conceptualisations, followed by a systematic review. Studies have supported positive outcomes of DSR, which can be favourable towards destinations at large. Although stakeholder theory is deemed foundational in conceptualizing DSR, findings reveal the construct has been studied from the perspective of tourists or residents, whereas other stakeholders are still absent from studies. The topic is biased towards quantitative methods and settings, and a comprehensive measurement instrument and definition of DSR are called for. This review aims to outline the contribution and progress of DSR in the context of responsible tourism, propose a unifying definition of DSR, and offer avenues for future research.